In-Situ observation of the oxygen nucleation in silicon with X-Ray single crystal diffraction - Will, Johannes; Gröschel, Alexander; Bergmann, Christoph; Magerl, Andreas (2011)
The measurement of Pendellosungs oscillations was used to observe the time dependent nucleation of oxygen in a Czochralski grown single crystal at 750 degrees C. It is shown, that the theoretical approach of the statistical dynamical theory describes the data well. Within the framework of this theory it is possible to determine the static Debye-Waller-factor as a function of the annealing time by evaluating the mean value of the Bragg intensity and the period length. The temperature influence on the Pendellosungs distance was corrected for by measurement of a Float-zone sample at the same temperature.
Keywords: Silicon; static Debye-Waller factor; statistical dynamical theory; single crystal diffraction; oxygen nucleation; in-situ; X-Ray; wedge shaped geometry; annealing